Foreign Direct Investment and Wage Spillovers in Indonesia - Sultoni, Sultoni (Jurnal Ilmiah Administrasi Publik, 2020)
This paper investigates the effect of Foreign Direct Investment (FDI) inflows on wage level paid by private domestic firms in Indonesia’s manufacturing sector. The previous literature focuses on horizontal linkages only. We develop this study by examining the spillover through horizontal and vertical channels. We find that there is strong evidence of horizontal and vertical wage spillovers from foreign to local firms in Indonesian manufacturing. However, after controlling for some firm characteristics, which are technology intensity level and firm size, we find that although vertical wage spillovers exist irrespective of the firm characteristics, horizontal spillovers show different results. This spillover is not present in relatively low technology level firms.